IMPLEMENTATION OF CHANNEL CODING SYSTEM AS ERROR CHECKING IN THE UNDERWATER COMMUNICATION SYSTEM USING AUDIO FREQUENCY - Nyoman Dheanty Maharani, Ni
In a digital communication system, information must have the same truth and ideal goals when sending information or receiving information. But in reality, this condition cannot always be realized due to the influence of interference both internally and externally. The interference effect can cause data corruption so that the information received will be different from the original information. In digital communication, this damage can be overcome with a coding system, one of them is called channel coding. Channel Coding is a bit coding technique by adding the performance of the data bits to be sent. Channel coding is divided into two parts, namely error detection coding, and error correction coding. In this system, CRC will be used as one of the error detection codings in channel coding. In the system, the CRC can perform error checking when the transmitter has sent data. The CRC will first perform calculations on the transmitter and send it in a hexadecimal form which will later be compared in the receiver whether the data sent is correct or not. If the data sent is correct, the receiver will get a notification that the data is valid. If not, then the receiver will get a notification that the data is invalid and advise the transmitter to resend the data. To support the channel coding system, the system will be tested using an acoustic modem consisting of an FSK modulator and an FSK demodulator. The test results show that this system has been able to perform error checking, but has not been able to tell the location of the error that occurred in the data.